Donald Campbell in speed boat (Module II, 2013)
England. Coniston. Footage of Donald Campbell on board his boat 'The Bluebird', during preparations in workshop. Campbell out on Lake Windermere during run in speed boat. When the boat comes to a stop, Campbell gets out of boat, helped by others, and poses with fans.